2022
DOI: 10.1002/anie.202204072
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Rotaxane‐Based Multi‐Modal Probes for Cancer Biomarker Imaging**

Abstract: Mechanically interlocked molecules present opportunities to construct therapeutic drugs and diagnostic imaging agents but harnessing supramolecular chemistry to make biologically active probes in water is a challenge. Here, we describe a rotaxane-based approach to synthesise radiolabelled proteins and peptides for molecular imaging of cancer biomarkers in vivo. Host-guest chemistry using β-cyclodextrin-and cucurbit-[6]uril-catalysed cooperative capture synthesis produced gallium-68 or zirconium-89 radiolabelle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Full details on the synthesis and characterisation of the precursors and [4]pseudorotaxane 1, the photochemical activation step, the radiochemistry and characterisation of both the 68 Ga-and 89 Zr-radiolabelled compounds were reported (see also Supporting Figures S1). 26 Simultaneous 89 Zr-radiolabelling and light-induced bioconjugation to onartuzumaban engineered monovalent antibody that binds the extracellular domain of the human hepatocyte growth factor receptor (c-MET) 30,31 afforded the [ 89 Zr]Zr- [4]semirotaxane-azepin-onartuzumab intermediate. Subsequent capping with FeCl3 and reaction quenching with diethylenetriamine pentaacetic acid (DTPA) gave the bimetallic full rotaxane-mAb conjugate, [ 89 Zr]ZrFe- [4]rotaxane-azepin-onartuzumab (Scheme 1, [ 89 Zr]ZrFe-2).…”
Section: Synthesis and Radiochemistrymentioning
confidence: 99%
See 4 more Smart Citations
“…Full details on the synthesis and characterisation of the precursors and [4]pseudorotaxane 1, the photochemical activation step, the radiochemistry and characterisation of both the 68 Ga-and 89 Zr-radiolabelled compounds were reported (see also Supporting Figures S1). 26 Simultaneous 89 Zr-radiolabelling and light-induced bioconjugation to onartuzumaban engineered monovalent antibody that binds the extracellular domain of the human hepatocyte growth factor receptor (c-MET) 30,31 afforded the [ 89 Zr]Zr- [4]semirotaxane-azepin-onartuzumab intermediate. Subsequent capping with FeCl3 and reaction quenching with diethylenetriamine pentaacetic acid (DTPA) gave the bimetallic full rotaxane-mAb conjugate, [ 89 Zr]ZrFe- [4]rotaxane-azepin-onartuzumab (Scheme 1, [ 89 Zr]ZrFe-2).…”
Section: Synthesis and Radiochemistrymentioning
confidence: 99%
“…S1). 26 Subsequent addition of protein to the reaction mixture (using an initial rotaxane-to-protein ratio of ~2:1), followed by pH adjustment, 32 and irradiation of the mixture with a powerful light emitting diode (LED, 395 nm, [ 89 Zr]ZrFe-2 was isolated with a d.c. RCY of 10.6%, an RCP of 90%, and an approximate 6-fold higher molar activity, with Am = 0.61 MBq nmol -1 of protein (6.176 MBq mg -1 of protein). The scaled-up reaction confirmed that the photoradiochemistry can be adapted to produce useful quantities of rotaxane-based radiotracers.…”
Section: Synthesis and Radiochemistrymentioning
confidence: 99%
See 3 more Smart Citations